Службы каталогов для хранения учетных записей пользователей - Корниенко, Б.Я.; Марутовская, Н.Н.; Шелепов, Е.О. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
This article examines the directory service, their characteristics and additional features tools for centralized storage facilities network.